2021
DOI: 10.3390/atmos12121653
|View full text |Cite
|
Sign up to set email alerts
|

Blowin’ in the Wind: Wind Dispersal Ability of Phytopathogenic Fusarium in a Wind Tunnel Experiment

Abstract: Dispersal processes play an essential role in cereal diseases caused by phytopathogenic Fusarium. However, most empirical studies of Fusarium spore dispersal have focused on vertical transport by rain splash, while wind dispersal has been mostly neglected. Our objective was to determine the ability of Fusarium conidiospores to disperse via wind under controlled conditions in a wind tunnel study. Ten Fusarium species with diverse spore varieties were studied by placing them in the wind stream at wind velocities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
8
1
Order By: Relevance
“…Propagules of Fusarium fungi are commonly distributed by wind, rain splash, or by arthropods [33,46,47]. However, a previous study investigating the dispersal of spores of different Fusarium species by wind suggests a combination of the different dispersal mechanisms [48]. The different spore types of the Fusarium fungi did not affect the probability to adhere to the body surface of the arthropods in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…Propagules of Fusarium fungi are commonly distributed by wind, rain splash, or by arthropods [33,46,47]. However, a previous study investigating the dispersal of spores of different Fusarium species by wind suggests a combination of the different dispersal mechanisms [48]. The different spore types of the Fusarium fungi did not affect the probability to adhere to the body surface of the arthropods in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…1,2 Fusarium genus has efficient mechanisms for conidia dispersal which has resulted in their global distribution. 3,4 Fusarium species are among the most important phytopathogenic fungi, responsible for significant losses in the agricultural fields worldwide. 5 Furthermore, the ability to produce a variety of toxic secondary metabolites such as trichothecenes, zearalenones, and fumonisins poses a significant threat to food safety and public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium species are filamentous ascomycete fungi that have a wide natural distribution 1,2 . Fusarium genus has efficient mechanisms for conidia dispersal which has resulted in their global distribution 3,4 . Fusarium species are among the most important phytopathogenic fungi, responsible for significant losses in the agricultural fields worldwide 5 .…”
Section: Introductionmentioning
confidence: 99%
“…There is limited information in the literature on the wind dispersal of different Fusarium species. In a wind tunnel experiment, Fusarium spores of different species exhibited different wind dispersal tendencies and indicated probable wind dispersal with carrier media or mobile linkers [ 57 ]. Kivlin et al [ 20 ] showed that dispersal was not the limiting filter for regional fungal composition in soil.…”
Section: Discussionmentioning
confidence: 99%